2022
DOI: 10.21037/atm-22-5703
|View full text |Cite
|
Sign up to set email alerts
|

Micro-ribonucleic acids (miRNAs) and a proteomic profile in lung adenocarcinoma cases with brain metastasis

Abstract: Background: Brain metastasis (BM) is the main cause of death of individuals with lung adenocarcinoma (LAC). Biomarkers with high sensitivity and specificity for the early detection and treatment of BM of LAC urgently need to be identified. In this study, we analyzed the pathogenesis of LAC-induced BM by detecting micro-ribonucleic acid (miRNA) and proteome expression differences between primary LAC lesion and BM tissue specimens to identify biomarkers of LAC-associated BM and develop potential therapeutic targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…At present, its pathogenesis is complex and unclear. Some studies have shown that mRNA and miRNA play important roles in the development of LUAD ( 27 , 28 ). A bioinformatics analysis showed that 4 differentially expressed miRNAs (i.e., miR-196b-5p, miR-223-3p, miR-135a-5p, and miR-9) and 4 differentially expressed mRNAs (i.e., MEIS1, HOXA5, SCARB1, and RUNX2) participate in the regulation network of the molecular mechanism of bone metastasis in LUAD ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…At present, its pathogenesis is complex and unclear. Some studies have shown that mRNA and miRNA play important roles in the development of LUAD ( 27 , 28 ). A bioinformatics analysis showed that 4 differentially expressed miRNAs (i.e., miR-196b-5p, miR-223-3p, miR-135a-5p, and miR-9) and 4 differentially expressed mRNAs (i.e., MEIS1, HOXA5, SCARB1, and RUNX2) participate in the regulation network of the molecular mechanism of bone metastasis in LUAD ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified a high-risk subtype of lung adenocarcinoma using genetic markers (1,(3)(4)(5)(6), while a study combining ribonucleic acid (RNA) and protein profiling identified pathways linked to brain metastasis in these patients (7). Abnormal expression of immune genes has been found to contribute to cancer progression (8)(9)(10), with immune factors linked to both brain metastasis and lung adenocarcinoma (11).…”
Section: Introductionmentioning
confidence: 99%